Churches by Enzo Fortuna (1921-1979) in Eastern Sicily between 1955 and 1970: Design Processes, Influences and Outcomes - Rosa Maria Marta Caruso (Histories of Postwar Architecture)
The piece focuses on the design of sacred architecture in Siracusa and in its surroundings through the study of the professional activity of Enzo Fortuna (1921-1979). The architect completed his studies in Rome in the late 1940s, and he worked in Sicily. Through Enzo Fortuna’s projects, such as the project for the competition for the sanctuary of Madonna delle Lacrime (1957), co-authored by Mario Tedeschi (1920-2005), and the design for the church of San Giuseppe in Cassibile (1957-1959) and the one of Cristo Re in Lentini (1959-1977), we recognize the vibrant discourse around sacred architecture during those years. Even smaller centers were not excluded from this discussion. The focus on architects operating in medium-small centers during the Reconstruction years provide insights into a series of historical-critical concepts traditionally based on exceptional samples. By examining the design processes of the selected projects, we identify references to contemporary famous architects, as well as significant changes in the design of sacred spaces due to the Second Vatican Council in 1962.